Green Biosynthesis of Silver Nanoparticles Using 'Polygonum Hydropiper' And Study Its Catalytic Degradation of Methylene Blue - Bonnia, NN; Kamaruddin, MS; Nawawi, MH; Ratim, S; Azlina, HN; Ali, ES (Elsevier Science Bv, 2024)
Indexed by WOS